Analysis of Ovarian Injury Associated With COVID-19 Disease in Reproductive-Aged Women in Wuhan, China: An Observational Study - Ding, Ting; Wang, Tian; Zhang, Jinjin; Cui, Pengfei; Chen, Zhe; Zhou, Su; Yuan, Suzhen; Ma, Wenqing; Zhang, Minli; Rong, Yueguang; Chang, Jiang; Miao, Xiaoping; et al. (Frontiers in Medicine, 2021)
Objective: This study was intended to investigate the relationship between COVID-19 disease and ovarian function in reproductive-aged women. Methods: Female COVID-19 patients of reproductive age were recruited between January 28 and March 8, 2020 from Tongji Hospital in Wuhan. Their baseline and clinical characteristics, as well as menstrual conditions, were recorded. Differentials in ovarian reserve markers and sex hormones (including anti-Müllerian hormone [AMH], follicle-stimulating hormone [FSH], the ratio of FSH to luteinizing hormone [LH], estradiol [E2], progesterone [P]，testosterone [T] and prolactin [PRL] were compared to those of healthy women who were randomly selected and individually matched for age, region and menstrual status. Uni- and multivariable hierarchical linear regression analyses were performed to identify risk factors associated with ovarian function in COVID-19 women. Results: 78 patients agreed to be tested for serum hormone, of whom 17 (21.79%) were diagnosed as the severe group and 39 (50%) were in the basal level group. Menstrual status (P= 0.55), menstrual volumes (P= 0.066), phase of menstrual cycle (P= 0.58) and dysmenorrhea history (P= 0.12) were similar without significant differences between non-severe and severe COVID-19 women. Significant lower serum AMH level/proportion (0.19/0.28 ng/ml vs 1.12 ng/ml, P=0.003/0.027; AMH≤1.1 ng/ml: 75%/70.4% vs 49.7%, P=0.009/0.004), higher serum T (0.38/0.39 ng/ml vs 0.22 ng/ml, P<0.001/0.001) and PRL (25.43/24.10 ng/ml vs 12.12 ng/ml, P<0.001/0.001) levels were observed in basal level and the all-COVID-19 group compared with healthy age-matched control. When adjusted for age, menstrual status and parity variations in multivariate hierarchical linear regression analysis, COVID-19 disease was significantly associated with serum AMH(β=-0.191；95%CI: -1.177-0.327; P=0.001), T(β=0.411；95%CI: 11.154-22.709; P<0.001) and PRL(β=0.497；95%CI: 10.787-20.266; P<0.001), suggesting an independent risk factor for ovarian function, which accounted for 3.2% of the decline in AMH, 14.3% of the increase in T, and 20.7% of the increase in PRL. Conclusion: Ovarian injury, including declined ovarian reserve and reproductive endocrine disorder, can be observed in women with COVID-19. More attention should be paid to their ovarian function under this pandemic, especially regarding reproductive-aged women.